Geomagnetic Observation Result, 2014-2015 - Benedetti, Giovanni; Cafarella, Lili; Lepidi, Stefania; Pietrolungo, Emanuela; Marzocchetti, Martina (2017)
This report deals with activities undertaken at the Antarctic Italian Geomagnetic Observatory during the austral summer 2014-2015. The coordinates of the Observatory at OASI are the following: Geographic latitude: 74.6936S Geographic longitude: 164.0975E Corrected Geomagnetic latitude (IGRF12): 79.85S Corrected Geomagnetic longitude (IGRF12): 306.57E Magnetic local time midnight: 08:18 UT This report describes the activities performed from October 30, 2014 to November 19, 2014. For the present work H, D and Z INTERMAGNET formatted data from the fluxgate magnetometer EDA have been used. The proton precession magnetometers used to record F total values were Overhauser type; for a description of instruments we refer to geomagnetism text books, for example Parkinson (1983) and Wienert (1970). Since the total intensity F time variations, at polar latitudes, where values of inclination is almost 90, are very close to the vertical component Z time variations, the plots of total intensity time variations are not shown. They can however be obtained from the well known equation: ingv Published 1A. Geomagnetismo e Paleomagnetismo 5IT. Osservatori